Financial Prerequisites for the Implementation of EU Directives at the Railway Transport in Ukraine - O. Ieromyna, M.; V. Dykan, V.; A. Karacharova, K.; G. Kirdina, O.; B.Bilous, L. (International Journal of Engineering and Technology, 2018)
The article analyzes the EU rail transport directives to be implemented in Ukraine after signing the Association Agreement between the EU and Ukraine, as well as the systematic positive and negative consequences and reservations of the implementation of the directives in the Ukrainian rail transport legislation. However, bringing of rail transport to the state declared in these directives requires significant investments including foreign ones. At the same time, the investment attractiveness of the railway industry is very low. The reason for this is the unsatisfactory state of the non-current assets, low quality of transportation, unprofitable passenger transportation which requires cross-subsidization, etc. Upgrade of the transport infrastructure should be carried out with the use of the latest energy efficient technologies. There is a need to change the management principles of the railway industry as a whole. Fulfilment of implementation conditions will trigger the attraction of investments and increase of the revenue part of the budget of Ukrzaliznytsia, which in turn will increase the competitiveness of the domestic railway.Â Â